Creative and active learning of the history of Islamic education using the near pod application - Abd Aziz Rekan; Tengku Sarina Aini Tengku Kasim; Asyraf Isyraqi Bin Jamil; Muhammad Nasir Mohamad Salleh; Nik Sofwatul Izzah Ishak; KhairulHamimah Mohammad Jodi (Jurnal Ilmiah Peuradeun, 2025)
The study of Islamic educational history, vital for intellectual society’s development, is often reduced to rote memorization, placing a cognitive burden on students and diminishing its contemporary relevance. This qualitative case study explored the potential of the Nearpod application to promote creative and active learning of Islamic educational history among Malaysian trainee teachers. Thematic analysis of reflections from 93 first-year trainee teachers revealed four key findings: Nearpod enhanced concentration and comprehension through engaging and interactive experiences; fostered a deeper emotional connection to Islamic history, making learning more meaningful; inspired trainee teachers to develop innovative approaches for teaching Islamic history; and presented challenges due to internet connectivity issues. Nearpod’s multimedia features - audio, video, and interactive questions—created an immersive learning environment, significantly improving understanding, motivation, and enthusiasm for continuous learning. Despite technological challenges, the integration of Nearpod transformed the teaching of Islamic history, addressing the urgent need for engaging and relevant pedagogical methods. These findings highlighted the potential of Nearpod to make Islamic educational history more accessible and impactful. The study’s results carried significant implications for teacher training programs and Islamic education, suggesting that technology-driven approaches could modernize traditional subjects effectively.